A Flexible Mobile Manipulator Architecture: A Case Study on Plasterboard Wall Preparation - Granat, Łukasz; Bryła, Michał; Kamiński, Kuba; Jędrzejczyk, Filip; Puchalski, Sławomir; Kessler, Ingmar; Perzylo, Alexander; Soriano, Ángel (Journal of Automation, Mobile Robotics and Intelligent Systems, 2026)
Skilled labor shortage and a competitive market are challenges for many businesses. Hence, automation and robotization are well-established in the large-scale, well-structured industrial environments of many factories. Moreover, there is a push for safer and more easily programmable robots, so-called cobots, that would be more suitable for smaller-scale applications. However, the implementation and customization of an overall robot system with different sensors, tools, external systems, etc. for the use cases of in particular small and medium-sized enterprises (SMEs) are still often infeasible. Therefore, this paper describes the design, implementation, and testing of a flexible mobile manipulator architecture with the following three abstraction layers. A high-level semantic layer models and utilizes OWL ontologies of abstract manufacturing processes, specific workcell environments, linked context knowledge, and the current semantic world state. An intermediate translation layer collects and exchanges data from multiple system components via a unified internal database, which is used, e.g., in combination with behavior trees to convert symbolic, high-level actions into multiple numeric, low-level commands, including their parameter values. A low-level control layer is implemented locally on a mobile robot to provide a unified interface of its potentially customized subsystems to the higher layers. This architectural approach facilitates the implementation of new use cases, e.g., by a system integrator, in that, e.g., the ontologies and behavior trees can be adapted on a flexible model level without changing source code. The implemented system was adapted to and deployed in five different real-world use cases of industrial partners during the VOJEXT project. This paper focuses on the plasterboard wall preparation use case from the construction domain as a guiding example, which includes taping, spraying, and sanding operations.